Aflatoxins in food and feed: Impacts risks, and management strategies - Brown, Lynn R. (International Food Policy Research Institute, 2018)
Aflatoxins are fungal metabolites—mainly produced by Aspergillus flavus and Aspergillus parasiticus living in soil—that contaminate crops throughout growth, harvest, storage, transportation, and processing. Aflatoxin B1 is not only the most potent natural carcinogen known, but also the most commonly produced toxic strain. As of 2010, roughly 5 billion people worldwide were estimated to be exposed to high levels of aflatoxins. High consumption levels can result in aflatoxicosis, which is often fatal. Habitual consumption at lower levels causes liver cancer and immune suppression, and is strongly associated with stunting. Of 315 cases of aflatoxicosis in Kenya in 2004, 125 people died. Consumption of aflatoxins is cumulative: they are not eradicated through standard cooking processes, and the body is unable to destroy or excrete them. This policy note examines what aflatoxins are; how they are linked to gender, climate change, and nutrition; and how they can be controlled and managed effectively.